Characterization of Ethanolic Extract of Saluang belum (Luvunga sarmentosa Kurz) Root - Gusti Rizaldi; Helmina Wati; Rahmi Muthia; Selvi Amadia; Farida Hayati; Pinus Jumaryatno (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2024)
Saluang belum (Luvunga sarmentosa Kurz) is a member of the endemic plants of Central Kalimantan, which the local community has traditionally used as a traditional medicine to cure several kinds of diseases. Characterization of the ethanolic extract of Saluang belum root is needed to facilitate the consistency of safety and quality. Therefore, this research needs to be carried out to complete the data on the characterization of the ethanolic extract of Saluang belum root. The material used is Saluang belum root collected from Palangkaraya, Central Kalimantan, Indonesia. There is no standard for Saluang belum extract. The results showed that name of the extract was Sarmentosa radix extractum; Indonesian name was Saluang belum; Latin name was Luvunga sarmentosa Kurz; part that used was root; reddish dark brown colour; typical smell; bitter flavour; contains carbohydrate, allylic alcohol and terpenoid compounds; density 0,82 g/ml; water content 4,865%; total ash content 1,74%; acid insoluble ash content 0,31%, negative residual solvent; Pb contamination 3,206 mg/kg; Cd contamination <0,001 mg/kg; total plate count 1,0 x 102 colonies/g; mold contamination 1,0 x 102 colonies/g; yeast contamination < 1,0 x 100 colonies/g.